Effect of very low-carbohydrate high-fat diet and high-intensity interval training on mental health-related indicators in individuals with excessive weight or obesity - Dominik Sindler; Tomas Dostal; Martina Litschmannova; Peter Hofmann; Lenka Knapova; Laura Maria König; Steriani Elavsky; Lukas Cipryan (Scientific Reports)
Abstract Very low carbohydrate high fat (VLCHF) diet and high-intensity interval training (HIIT) are widely utilized for weight reduction and cardiorespiratory fitness improvement, respectively. To assess the acceptability of these approaches, it is essential to examine mental health-related indicators. This secondary analysis of a randomized controlled trial investigated the isolated and synergistic effects of VLCHF and HIIT on mental health-related indicators in individuals with excessive weight or obesity. Sixty-eight participants (age = 42 ± 10.2; 20–60 years; BMI = 29.8 ± 3.7) were analysed across four groups: HIIT (n = 15, 4 males, 11 females), VLCHF (n = 19, 4 males, 15 females), VLCHF + HIIT (n = 19, 4 males, 15 females), and control (n = 15, 4 males, 11 females). The 12-week intervention, involved VLCHF diet or HIIT sessions, depending on group affiliation and completing online questionnaires via Qualtrics software before and after the intervention. The questionnaires included the 12-item Short Form Survey (SF-12) for mental (MHS) and physical health scores (PHS), the Satisfaction with Life Scale (SWLS), and the Perceived Stress Scale (PSS). Using the Kruskal–Wallis test, we found no significant differences in mental health-related indicators between groups after 12 weeks, except for SWLS (p = 0.031; ES = 0.133; medium), which improved significantly in the VLCHF + HIIT group compared to the HIIT group. Our findings indicate that HIIT and VLCHF, alone or combined, do not significantly affect mental health-related indicators.